The Potential of the ePortfolio as a Recruitment Tool: From the Perspective of HR Directors - Ciesielkiewicz, Monika; Bonilla, Claire; Olave López de Ayala, Carlos (International Journal of Interactive Mobile Technologies (iJIM), 2020)
In this paper, the authors explore the potential of the electronic portfolio (ePortfolio) as a recruitment tool, in particular whether Human Resources directors would be willing to use it during the recruitment and selection process. The ePortfolio presents, documents, reflects on, and fosters students’ skills, credentials, certificates and diverse formal and informal experiences in a structured and well-organized manner. Because the ePortfolio is, by nature, flexible and adaptable, an ePortfolio developed with the help of professors over the course of a students’ studies can easily be incorporated into professional networking platforms as a job search tool and showcase the skills required for a successful applicant. It is often said that the difference between what is taught in the academic world and the practical skills that are required by the business sector make it difficult for students to access the labor market. The ePortfolio may help to reconcile both worlds. In order to examine whether Human Resources directors are willing to use an ePortfolio as a recruitment tool, a survey was carried out among fifty-two Human Resources directors. The research findings reveal that an educational ePortfolio can count on significant approval in the business sector. This research study is relevant as it provides valuable information on this topic and it is the only one to date, conducted among HR directors in the context of Spanish-speaking countries.